Impact of overexpression of 9-cis-epoxycarotenoid dioxygenase on growth and gene expression under salinity stress - Martínez-Andújar, Cristina; Martínez-Pérez, Ascensión; Ferrández-Ayela, Almudena; Albacete, Alfonso; Martínez-Melgarejo, Purificación A.; Dodd, Ian C.; Thompson, Andrew J.; Pérez, José Manuel; Pérez-Alfocea, Francisco (Elsevier, 2019)
To better understand abscisic acid (ABA)’s role in the salinity response of tomato (Solanum lycopersicum L.), two independent transgenic lines, sp5 and sp12, constitutively overexpressing the LeNCED1 gene (encoding 9-cis-epoxycarotenoid dioxygenase, a key enzyme in ABA biosynthesis) and the wild type (WT) cv. Ailsa Craig, were cultivated hydroponically with or without the addition of 100 mM NaCl. Independent of salinity, LeNCED1 overexpression (OE) increased ABA concentration in leaves and xylem sap, and salinity interacted with the LeNCED1 transgene to enhance ABA accumulation in xylem sap and roots. Under control conditions, LeNCED1 OE limited root and shoot biomass accumulation, which was correlated with decreased leaf gas exchange. In salinized plants, LeNCED1 OE reduced the percentage loss in shoot and root biomass accumulation, leading to a greater total root length than WT. Root qPCR analysis of the sp12 line under control conditions revealed upregulated genes related to ABA, jasmonic acid and ethylene synthesis and signalling, gibberellin and auxin homeostasis and osmoregulation processes. Under salinity, LeNCED1 OE prevented the induction of genes involved in ABA metabolism and GA and auxin deactivation that occurred in WT, but the induction of ABA signalling and stress-adaptive genes was maintained. Thus, complex changes in phytohormone and stress-related gene expression are associated with constitutive upregulation of a single ABA biosynthesis gene, alleviating salinity-dependent growth limitation.
Keywords: Abscisic acid; 9-cis-epoxycarotenoid dioxygenase; plant hormones; root gene expression; salt stress; tomato (Solanum lycopersicum)